Key themes in public health: - Thurston, Miranda (Routledge, 2014)
"Key Themes in Public Health consists of introductory short essays exploring fifty key themes and concepts in public health. Ranging from political and economic concern with improving population health and reducing health inequalities, to debates about how to protect the population from new health threats, as well as a concern with individual responsibility for lifestyles and behaviour, the themes discussed include: determinants of health; globalisation; evidence; risk and population. Presenting provocative ways of thinking about key ideas in a concise fashion, each essay provides a basic grounding in the relevant theme as well as a departure point for further study by: Defining the theme in an accessible way, Illustrating its application and significance in the field, Identifying and exploring issues surrounding each of the themes, Providing several references for further reading. This text provides an accessible overview for students new to public health who want to get to grips with the full range and complexity of this diverse and multidisciplinary field"--